2013
DOI: 10.1016/s1474-4422(12)70238-7
|View full text |Cite
|
Sign up to set email alerts
|

Endoplasmic reticulum dysfunction in neurological disease

Abstract: Endoplasmic reticulum (ER) dysfunction is important in the pathogenesis of many neurological diseases. In this review, we examine the evidence for ER dysfunction in a range of neurological conditions including cerebral ischaemia, sleep apnoea, Alzheimer's disease, multiple sclerosis, amyotrophic lateral sclerosis, the prion diseases and Familial Encephalopathy with Neuroserpin Inclusion Bodies (FENIB). Protein misfolding in the endoplasmic reticulum initiates a well-studied 'Unfolded Protein Response' in energ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
315
0
4

Year Published

2014
2014
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 414 publications
(326 citation statements)
references
References 140 publications
7
315
0
4
Order By: Relevance
“…Chronic ER stress has been implicated in neuronal disorders causing neurodegeneration and cognitive dysfunction. [25][26][27][28] SCI causes increased levels of markers of ER stress, which is a known component of secondary injury. [29][30][31] However, no studies have examined whether or how SCI can induce ER stress responses in cortex or hippocampus or whether such changes may contribute to neurobehavioral consequences.…”
Section: Introductionmentioning
confidence: 99%
“…Chronic ER stress has been implicated in neuronal disorders causing neurodegeneration and cognitive dysfunction. [25][26][27][28] SCI causes increased levels of markers of ER stress, which is a known component of secondary injury. [29][30][31] However, no studies have examined whether or how SCI can induce ER stress responses in cortex or hippocampus or whether such changes may contribute to neurobehavioral consequences.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, increasing evidence suggests that AD and OSA pathogenesis includes strong interactions with immunological mechanisms in the brain (Heneka et al, 2015a,b;Rosenzweig et al, 2015). Genome-wide analysis further suggest that several genes that increase the risk for sporadic AD also encode factors that regulate glial clearance of misfolded proteins and the inflammatory reaction (Heneka et al, 2015a) Comparably, abnormal protein folding and neuroinflammation have been also demonstrated or suggested by preclinical and clinical OSA studies (Roussel et al, 2013;Rosenzweig et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…In regard to tau tangles, activated components of the UPR frequently co‐localize with hyperphosphorylated tau. Further mechanistic analyses have shown that phosphorylation of PERK activates its downstream kinase GSK‐3β, which in turn leads to the hyperphosphorylation of tau and facilitates the formation of tau tangles (Roussel, Kruppa, Miranda, Crowther, & Lomas, 2013). Meanwhile, due to the excessive burden on the ER, the UPR could also trigger apoptotic death of affected neurons, which is a vital mechanism of neuronal death in AD‐affected regions (Li, Yu, Jiang, & Tan, 2015; Xiang et al., 2017) (3; 5).…”
Section: The Important Role Of Protein Synthesis Pathways In Cancer Amentioning
confidence: 99%